Literature Review : The Effects of Antioxidant Saponins in Herbal Plants on Testicular Histology of Rats with Diabetes Mellitus and The Review of Islamic Perspective - Jean Kharismatik Persada; Etty Widayanti; Aan Royhan (Junior Medical Journal, 2023)
Introduction: Diabetes mellitus is a metabolic disorder. Diabetes mellitus can cause a decrease in sperm count, sperm motility, testosterone hormone, erectile ability, libido and testicular weight. Antidiabetic drugs consumed long-term can cause side effects; therefore, alternative treatment is needed using herbal medicinal plants. Saponins in plants are a complex class of complex natural compounds with a large molecular mass, namely steroid or triterpenoid aglycones with one or more sugar/glycoside chains. Saponins function as antioxidants. This study aims to determine the effect of saponins as one of the antioxidants on the testicular organs of rats (Rattus norvegicus) Wistar strain-induced Streptozotocin. Methods: This study used the Literature Review method with a narrative literature review type. The data collection technique uses a search for several research databases through Google Scholar and Mendeley. This research has four journals that will review. Results: The results showed that herbal plants have bioactive compounds such as flavonoids, alkaloids, terpenoids, tannins, and saponins that have antidiabetic effects with different mechanisms in reducing blood glucose levels repairing damage to testicular tissue of diabetes mellitus rats. Conclusion: Antioxidant saponins in herbal plants influence improving and supporting the repair of testicular histology damage in diabetic cases. Allah SWT grows a wide variety of plants that have enormous benefits for humans, including food and medicine, because Allah SWT created various kinds of plants with multiple uses.